PENGARUH KARAKTERISTIK PETERNAK SAPI BALI TERHADAP TINGKAT ADOPSI INSEMINASI BUATAN DI KECAMATAN RENDANG KABUPATEN KARANGASEM (The influence of bali cattle farmer’s characteristics on the adoption level of artificial insemination in Rendang District, ..) - Adiputra, I Putu; Sumardani, Ni Luh Gde; Sukanata, I Wayan (Universitas Nusa Cendana, 2024)
The level of adoption Artificial Inseminatioan (AI) can be influenced by the characteristics of farmer in raising Bali cattle. This research aims to determine the level of adoption of artificial insemination (AI) and the influence of the characteristics of Bali cattle farmers on the adoption of AI in the Rendang District, Karangasem Regency. This study is a survey with 90 farmer respondents. The type of research is quantitative explanatory aimed at explaining the relationship and influence of each variabel. The data sources used are primary and secondary data. Data collection methods include observation, interviews, and documentation. The analysis used in this study is multiple linear regression aimed at determining the influence of farmer characteristic variabels (independent) on the level of adoption of AI (dependent). The research results show that the adoption rate of AI by Bali cattle farmers in the Rendang District, based on knowledge, interest, evaluation, trial, and implementation of AI technology is high at 86.8%. The influence of Bali cattle farmers characteristics on the adoption of AI in terms of non-formal education (X1) is 11.62%, farming experience (X2) is 14.70%, the number of livestock ownership (X3) is 26.05%, and the number of family dependents (X4) is 18.94% on the adoption of AI. The conclusion of this study is that the adoption rate of AI by farmers in the Rendang District is relatively high and is significantly influenced by the number of livestock ownership (X3) at 26.05%.